Multiple tubulins: evolutionary aspects and biological implications. (18th June 2013) - Breviario, Diego; Gianì, Silvia; Morello, Laura
Summary Plant tubulin is a dimeric protein that contributes to formation of microtubules, major intracellular structures that are involved in the control of fundamental processes such as cell division, polarity of growth, cell‐wall deposition, intracellular trafficking and communications. Because it is a structural protein whose function is confined to the role of microtubule formation, tubulin may be perceived as an uninteresting gene product, but such a perception is incorrect. In fact, tubulin represents a key molecule for studying fundamental biological issues such as (i) microtubule evolution (also with reference to prokaryotic precursors and the formation of cytomotive filaments), (ii) protein structure with reference to the various biochemical features of members of the FstZ/tubulin superfamily, (iii) isoform variations contributed by the existence of multi‐gene families and various kinds of post‐translational modifications, (iv) anti‐mitotic drug interactions and mode of action, (v) plant and cell symmetry, as determined using a series of tubulin mutants, (vi) multiple and sophisticated mechanisms of gene regulation, and (vii) intron molecular evolution. In this review, we present and discuss many of these issues, and offer an updated interpretation of the multi‐tubulin hypothesis.